Factors of job insecurity and their relationship with the health of workers (Ciencias de la Ingeniería y Aplicadas, 2021)
This research project is aimed at knowing the factors of job insecurity in the different employment characteristics, with the objective of determining the risks and diseases that have the greatest impact on the worker, carrying out an analysis by collecting information from studies carried out specifically of the country, in addition to selecting research carried out by other authors with the purpose of supporting the object investigated. Therefore, the application of bibliographic methods is necessary for the effective completion of the project. The importance of the project focuses on demonstrating how the poor working conditions to which workers in Ecuador are exposed affect health so that future research can take measures and thus be able to protect their safety and health. The following results have been obtained regarding job insecurity in Ecuador, showing that in recent years.
Keywords: Job Insecurity; Health; Risks; Diseases